B cell metabolism in autoimmune diseases: signaling pathways and interventions - Li, Jingyue; Zhao, Mingjiu; Luo, Wenjun; Huang, Jiaqi; Zhao, Bin; Zhou, Zhiguang (Frontiers in Immunology, 2023)
Autoimmune diseases are heterogeneous disorders believed to stem from the immune system's inability to distinguish between auto-and foreign-antigensthought to result from the immune system's failure to distinguishrecognize between auto-and foreignantigens. B lymphocytes serve a crucial role in humoral immunityB lymphocytes have a vital function in humoral immunity as they generate antibodies and present antigens. cells are crucial components of the immune system, producing antibodies and presenting antigens. Dysregulation of B cell function induce the onset of autoimmune disorders by generating autoantibodies and pro-inflammatory cytokines, resulting in an imbalance in 2 immune regulation.leads to the development of autoimmune diseases through the production of autoantibodies and pro-inflammatory cytokines. New research in immunometabolism shows that cellular metabolism plays a criticalan essential role in regulatingcontrolling B celllymphocytes immune responsesreactions by providing the energy and substrates necessary vital for B celllymphocytes activation, differentiation, and function. However, dysregulated immunometabolism lead to autoimmune diseases by disrupting self-tolerance mechanisms. In thisThis review, we summarize summarizes the latest research on metabolic reprogramming of B cellslymphocytes in autoimmune diseases, identifying crucial pathways and regulatory factors. Moreover, we consider the potential of metabolic interventions as a promising therapeutic strategy. Understanding the metabolic mechanisms of B cells brings us closer to developing novel therapies for autoimmune disorders.Additionally, we discussexplore the potential of metabolic interventions as a promising therapeutic strategyapproach. Understanding B cell metabolic mechanisms aid in creating new therapies for autoimmune diseasesdisorders.